Mapping of pedagogical training of university professors in Portuguese public universities - Xavier, Amanda Rezende Costa [UNESP] (2019)
The recent transformations in higher education, associated with the Bologna Process, imposed a curricular reform that, among other aspects, points to a reconfiguration of teaching pedagogical practices. The political discourse conveyed affirms a rupture with the paradigm supported in the transmission of knowledge, to privilege the action of the students in the construction of their own learning. This scenario, which emerges from the Bologna Process, is the foundation for a study that answers the question: what attention is given by the Portuguese public universities, to the creation of spaces for the construction of teaching knowledge where teachers can develop skills to respond to the curricular challenges of the Bologna Process? The study collected data through the institution’s electronic pages, related to strategic and action plans, as well as the sectors responsible for teacher education, and their training agendas, from13 of the 14 Portuguese public universities. The content analysis of these data showed that, although with institutional structures that deal with this pedagogical dimension, the way they are allocated in the universities organization and competences, show a distinct level of commitment of their teacher’s education. There are those that demonstrate being in the phase of the implementation of projects that may result in institutional formative spaces, but also those that do not yet deal with the issue of pedagogical training and teaching support.